Violence Against Women and Girls : Health Sector Brief - Gennari, Floriza; McCleary-Sills, Jennifer; Arango, Diana; Hidalgo, Nidia (World Bank, Washington, DC, 2015)
Violence against women and girls (VAWG) has negative impacts on physical and mental health. Health care settings provide a unique opportunity to identify VAWG survivors, provide critical support services, and prevent future harm. VAWG has intergenerational effects: boys who witness intimate partner violence (IPV) at home are more likely to grow up to perpetrate violence themselves. And girls with childhood exposure to IPV are more likely to experience violence in later relationships. The health sector can play a role in educating clients and the broader community about VAWG as a human rights violation and major public health issue.